2021
DOI: 10.1186/s12889-021-11012-3
|View full text |Cite
|
Sign up to set email alerts
|

ADVANCE integrated group intervention to address both substance use and intimate partner abuse perpetration by men in substance use treatment: a feasibility randomised controlled trial

Abstract: Background Substance use is a risk factor for intimate partner abuse (IPA) perpetration. Delivering perpetrator interventions concurrently with substance use treatment shows promise. Methods The feasibility of conducting an efficacy and cost-effectiveness trial of the ADVANCE 16-week intervention to reduce IPA by men in substance use treatment was explored. A multicentre, parallel group individually randomised controlled feasibility trial and forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…A feasibility randomised controlled study of the ADVANCE group intervention plus substance use treatment as usual (TAU) compared to substance use TAU only was conducted with 104 men in substance use treatment in England [ 28 ] and outcomes assessed 16-weeks post-randomisation. Findings highlighted that it was feasible to deliver the face-to-face ADVANCE group intervention and that the intervention was safe and resulted in positive behaviour change [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A feasibility randomised controlled study of the ADVANCE group intervention plus substance use treatment as usual (TAU) compared to substance use TAU only was conducted with 104 men in substance use treatment in England [ 28 ] and outcomes assessed 16-weeks post-randomisation. Findings highlighted that it was feasible to deliver the face-to-face ADVANCE group intervention and that the intervention was safe and resulted in positive behaviour change [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous eligibility rate (7%) of men approached in waiting rooms by researchers was low [ 29 ]. Therefore, men will now be identified and screened by substance use treatment staff.…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the need for integrated interventions and underline the importance of the current ADVANCE programme. ADVANCE targets low-medium risk perpetrators, working with those argued to fall into the entrenched substance use pathway and some in the relationship insecurity pathway (Dheensa et al, 2021;Gilchrist et al, 2021b). The programme draws on elements of cognitive behavioural therapy, dialectical behavioural therapy and behavioural approaches to address behaviour, cognition and emotion elements of substance use related IPA (Gilchrist et al, 2021a, b).…”
Section: Future Steps and Practical Implicationsmentioning
confidence: 99%
“…This intervention development led onto a feasibility randomised controlled trial (RCT) among 104 male perpetrators attending substance use treatment in England. The full details are reported elsewhere [ 14 , 24 ], but in brief this study identified that it was possible for trained substance use staff to deliver the ADVANCE intervention in substance use treatment services and that men who attended and staff who delivered the intervention evaluated it highly. Following this, a full-scale, multi-site randomised controlled trial to compare the effectiveness of the ADVANCE intervention plus substance use treatment as usual (TAU) to substance use TAU only, and a nested process evaluation will explore the ‘what works and how and for whom’ was planned.…”
Section: Discussionmentioning
confidence: 99%